Barāqish/Yathill (Yemen) 1986-2007 - Antonini, Sabina,; Fedele, F. G. (Archaeopress Archaeology, 2021)
This richly illustrated volume presents the remarkable results of the Italian Archaeological Mission's investigations at the site of the walled town of Baraqish in interior Yemen, ancient Yathill of the Sabaeans and Minaeans, between 1986 and 2007.